2015
DOI: 10.1039/c4ee03746d
|View full text |Cite
|
Sign up to set email alerts
|

Promoted C–C bond cleavage over intermetallic TaPt3 catalyst toward low-temperature energy extraction from ethanol

Abstract: Intermetallic TaPt3 nanoparticles promote C–C bond cleavage in ethanol and exhibit much higher catalytic performance than traditional catalysts for the ethanol electrooxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 40 publications
1
30
0
Order By: Relevance
“…By incorporating a more electropositive and oxyphilic metal such as Nb or Ta into Pt‐based intermetallic nanocrystals, complete electro‐oxidation of ethanol is promoted since the second metal can more favorably generate additional OH species from water . In a recent study, Abe and co‐workers evaluated the EOR properties of Pt 3 Ta intermetallic nanocrystals relative to the commercial Pt/C and Pt 3 Sn/C, showing a much lower onset potential, higher current density, and longer cycling life for the intermetallic catalysts . Both CO stripping tests and DFT calculations showed that the substantially enhanced EOR properties could be attributed to the significantly weakened CO chemisorption on the Pt 3 Ta intermetallic surface and the strengthened structure stability arising from the low formation enthalpy.…”
Section: Catalytic Applications Of Intermetallic Nanocrystalsmentioning
confidence: 99%
“…By incorporating a more electropositive and oxyphilic metal such as Nb or Ta into Pt‐based intermetallic nanocrystals, complete electro‐oxidation of ethanol is promoted since the second metal can more favorably generate additional OH species from water . In a recent study, Abe and co‐workers evaluated the EOR properties of Pt 3 Ta intermetallic nanocrystals relative to the commercial Pt/C and Pt 3 Sn/C, showing a much lower onset potential, higher current density, and longer cycling life for the intermetallic catalysts . Both CO stripping tests and DFT calculations showed that the substantially enhanced EOR properties could be attributed to the significantly weakened CO chemisorption on the Pt 3 Ta intermetallic surface and the strengthened structure stability arising from the low formation enthalpy.…”
Section: Catalytic Applications Of Intermetallic Nanocrystalsmentioning
confidence: 99%
“…This example highlights how a nanoarchitectonic approach can preserve functionally active lattice structures while transforming common CuO into a high‐performance material resembling precious Pt and Rh. Additionally, efficient control of the metallic atom composition with lattice engineering can modulate the catalytic of intermetallic TaPt 3 nanoparticles for realizing the electrooxidation of ethanol to CO 2 and mixed‐valence tin oxide, (Sn 2+ ) 2 (Sn 4+ )O 4 , for photocatalytic hydrogen evolution from aqueous solutions …”
Section: Nanomaterials Platformmentioning
confidence: 99%
“…TEMPO,aredox mediator,plays apivotal role in facilitating the reaction to ensure the stability of the anchored dye and the selectivity of the desired oxidation product. Adding ar edox mediator might be especially useful for photoredox catalysts that exhibit excellent photochemical activity but are not stable under aerobic oxidation conditions.Accounting for the fact that the oxidation chemistry of TEMPO is everexpanding and interesting catalytic systems based on metal oxides and intermetallic materials are rapidly developing, [17] we are seeking better examples similar to the current dyesensitized TiO 2 photoredox catalysis setup in due course.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Adding ar edox mediator might be especially useful for photoredox catalysts that exhibit excellent photochemical activity but are not stable under aerobic oxidation conditions.Accounting for the fact that the oxidation chemistry of TEMPO is everexpanding and interesting catalytic systems based on metal oxides and intermetallic materials are rapidly developing, [17] we are seeking better examples similar to the current dyesensitized TiO 2 photoredox catalysis setup in due course. TEMPO,aredox mediator,plays apivotal role in facilitating the reaction to ensure the stability of the anchored dye and the selectivity of the desired oxidation product.…”
mentioning
confidence: 99%